Anti-inflammatory actions of Pentosan polysulfate sodium in a mouse model of influenza virus A/PR8/34-induced pulmonary inflammation - Krishnan, Ravi; Stapledon, Catherine J. M.; Mostafavi, Helen; Freitas, Joseph R.; Liu, Xiang; Mahalingam, Suresh; Zaid, Ali (Frontiers in Immunology, 2023)
There is an unmet medical need for effective anti-inflammatory agents for the treatment of acute and post-acute lung inflammation caused by respiratory viruses. The semi-synthetic polysaccharide, Pentosan polysulfate sodium (PPS), an inhibitor of NF-kB activation, was investigated for its systemic and local anti-inflammatory effects in a mouse model of influenza virus A/PR8/1934 (PR8 strain) mediated infection. In the acute phase of PR8 infection in C57BL/6J mice, PPS treatment was associated with a reduction in weight loss and improvement in oxygen saturation when compared to vehicle-treated mice. Associated with these clinical improvements, PPS treatment showed a significant retention in the numbers of protective SiglecF+ resident alveolar macrophages, despite uneventful changes in pulmonary leukocyte infiltrates assessed by flow cytometry. PPS treatment in PR8- infected mice showed significant reductions systemically but not locally of the inflammatory molecules, IL-6, IFN-gamma, TNF-alpha, IL-12p70 and CCL2. In the post-acute phase of infection, PPS demonstrated a reduction in the pulmonary fibrotic biomarkers, sICAM-1 and complement factor C5b9. In conclusion, the systemic and local anti-inflammatory actions of PPS may regulate acute and post-acute pulmonary inflammation and tissue remodelling mediated by PR8 infection, which warrants further investigation.